THE EFFECT OF ENGLISH COMICS ON THE STUDENTSâ€™ VOCABULARY ACHIEVEMENT AT SECOND YEAR STUDENTS OF SMP NEGERI 10 KENDARI - Zahra, Risya Fatimah (Journal of Teaching of English, 2019)
This study is conducted to investigate whether there was a significant effect of English comics on studentsâ€Ÿ vocabulary achievement. The research question of this study was â€œis there any significant effect of English comics on studentsâ€Ÿ vocabulary achievement at SMPN 10 Kendari?â€ The design of this study was quasi experimental design that consists of experimental class and control class. The sample of this study are students at class VIII 3 and VIII 4 in SMP Negeri 10 Kendari who register in academic year 2016/2017 with the total number of sample are 56 students, 27 for control class and 29 for experimental class. The instrument of this study is a vocabulary test. The researcher collects the data by giving pre test in two classes to know students ability, giving treatment which Â the researcher conducted teaching and learning process by using English comics in experimental class and using no media (conventional teaching method) in control class, giving post test to know studentsâ€Ÿ vocabulary achievement after being taught by using comics compared with the result in class that taught by conventional teaching media. The researcher used an Independent sample T-test in SPSS verse 20 to analyze the result of the research. An independent sample t-test was conducted to compare the gain scores in experimental and control class. There was a significant difference in the scores for experimental class (M= 2.02, SD= 2.03) and control class (M= 0.94, SD= 1.32) conditions; p= 0.02 Sig. <Î± or H0 Â is rejected and H1 Â is accepted.Â  Thus,Â  it Â can be saidÂ  that Â using EnglishÂ  comics Â has Â increasedÂ  the Â studentsâ€Ÿ Â vocabulary achievement. The effect of English comics can increase studentsâ€Ÿ vocabulary achievement at second year studentsâ€Ÿ of SMPN 10 Kendari.Â Keywords : English comics, Vocabulary Achievement, Media in Learning